'They never talked to me about…': Perspectives on aged care resident transfer to emergency departments. (26th December 2013) - Arendts, Glenn; Popescu, Aurora; Howting, Denise; Quine, Susan; Howard, Kirsten
<x xml:space="preserve">Abstract</x> Aims To explore perspectives of three groups concerning transfers from aged care facilities to emergency departments. We sought to reveal factors influencing transfer decisions; how active each group was in making decisions; and to what extent groups ceded decision‐making to others. Methods Semi‐structured interviews of 11 residents, 14 relatives and 17 staff with content analysis of interview transcripts. Results The three groups substantially differed in their involvement with initiating, and attitudes towards, transfer. Residents were least likely to be involved in the decision, yet most likely to support transfer. Staff felt conflicted between their desire to provide optimal treatment for one ill resident, and their obligations to other residents under care. Staff perspectives were largely consistent with published data, but we describe new results for other informant groups. Conclusions Group expectations and preferences differ substantially. Service delivery to meet all preferences presents a challenge for health service design.